Geographic information system as a tool for assessing ponds and the potential for environmental impact caused by fish farming - Felipe Silva Morsoleto; Karen Carrilho da Silva Lira; Jhony Ferry Mendonça da Silva; Humberto Rodrigues Francisco; Fabio Bittencourt; Aldi Feiden (Boletim do Instituto de Pesca)
The hydrographic basin of Arroio Marreco (Paraná State) concentrates a productive chain of fish farming and great intensification of tilapia farming. In this study, we aimed to monitor the quality of effluent water and organic and inorganic elements released by fish farming in ponds, using geomorphological and land-use and occupation data. The Terrain Analysis Using Digital Elevation Models, Digital Elevation Model software was used to delimit watersheds in the software Quantum geographic information system version 3.6.3. A total of 1,457 production units (water slides) were identified across the study area. This represented an occupied area of 160.2 ha. Analyzing the sub-basins, it was found that High Marreco is the sub-basin with the most developed logistical chain. Low Marreco does not yet have an integration of its fish farming with the regionââ‚¬â„¢s logistics chain. Medium Marreco does not have fish farming as its main activity, only using it to reuse inputs from other agricultural activities. There is a large input of nutrients from aquaculture in all the sub-basins. To reduce them, it is recommended to implement decantation and/or reuse of wastewater systems. The results of this study show how important it is to know the dynamics of nutrients in the fish farms and the physical characteristics of the drainage basin to determine the support capacity of the environment, so as not to allow licenses that promote impacts above the self-cleaning capacity of the courses water.